Laser-Induced Modification of Hydrogenated Detonation Nanodiamonds in Ethanol - Bydzovska, Irena; Shagieva, Ekaterina; Gordeev, Ivan; Romanyuk, Oleksandr; Nemeckova, Zuzana; Henych, Jiri; Ondic, Lukas; Kromka, Alexander; Stehlik, Stepan (Nanomaterials (Basel, Switzerland), 2021)
Apart from the frequently used high-temperature annealing of detonation nanodiamonds (DNDs) in an inert environment, laser irradiation of DNDs in a liquid can be effectively used for onion-like carbon (OLC) formation. Here, we used fully de-aggregated hydrogenated DNDs (H-DNDs) dispersed in ethanol, which were irradiated for up to 60 min using a 532 nm NdYAG laser with an energy of 150 mJ in a pulse (5 J/cm2) at a pulse duration of 10 ns and a repetition rate of 10 Hz. We investigated the DND surface chemistry, zeta potential, and structure as a function of laser irradiation time. Infrared spectroscopy revealed a monotonical decrease in the C-Hx band intensities and an increase of the C-O and C=O features. Transmission electron microscopy (TEM) revealed the formation of OLC, as well as a gradual loss of nanoparticle character, with increasing irradiation time. Surprisingly, for samples irradiated up to 40 min, the typical and unchanged DND Raman spectrum was recovered after their annealing in air at 450 °C for 300 min. This finding indicates the inhomogeneous sp3 to sp2 carbon transformation during laser irradiation, as well as the insensitivity of DND Raman spectra to surface chemistry, size, and transient structural changes.
Keywords: laser; Raman spectroscopy; surface chemistry; structure; carbon nano-onion; nanodiamond; onion-like carbon; zeta potential